The Follow-Up of Dietary Treatment of Obesity - Buscemi, Silvio; Verga, Salvatore (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2008)
Obesity is a disease with an acknowledged high metabolic and cardiovascular risk, however, only recent studies demonstrated that the dietary treatment of obesity consisting of lifestyle modification programs may be successful in the long run. As for any therapeutic procedure, the dietary hypocaloric treatment of obesity has results and objectives to be verified and surveillance is needed as far as it concerns safety and tolerability. The epidemic of obesity is spreading to impressive levels in the western world; therefore, the treatment of obesity must be cost-effective in order to reach as much people is possible, even for the aspects relative to the follow-up. Unfortunately, there are not significant official guidelines at this regard. In this article, we report the procedures of follow-up as presented in the recent long-term clinical trials that demonstrated the efficacy of the treatment of obesity. Recent patent related to the field are also discussed.
Keywords: efficacy